Impacts of geopolitical risks and economic policy uncertainty on Chinese tourism‐listed company stock. (28th August 2020) - Jiang, Yonghong; Tian, Gengyu; Wu, Yiqi; Mo, Bin
Abstract: This paper investigates how geopolitical risk (GPR) and economic policy uncertainty (EPU) impact the Chinese tourism stock return using the quantile‐on‐quantile method and causality‐in‐quantiles approach. Compared to the conventional linear regression model and the quantile regression, the quantile‐on‐quantile method can capture more factors of uncertainty and provide more accurate and detailed empirical results. Besides, we consider the upper quantile and lower quantile of stock return as the tourism peak season and off‐season respectively. Overall, the empirical results indicate GPR exerts a lasting negative effect on tourism stock return and that the negative effect of GPR at low quantile is more significant than that at high quantile. Besides, the Chinese categorical EPU influences both negatively and positively the stock returns at different distribution levels. And during tourist off‐season, the asymmetric phenomena between GPR, EPU and stock return are more obvious at lower quantiles and upper quantiles.